Neuropathic Component Characteristics in Chronic Secondary Musculoskeletal Pain After Postmenopausal Osteoporotic Fractures: A Pilot Cross-Sectional Study - Marie-Eva Pickering; Serge Perrot; Dualé Christian; Véronique Morel; Nicolas Macian; Bruno Pereira (Pain Research and Management)
Conclusions: Future research should focus on the neuropathic characteristics of pain patients with OP, in order to better manage OP-related pain.